POLICY TO SUPPORT THE FINANCING OF MICROENTREPRENEURS - Théogène, Nsengiyumva (Universitas Nusa Cendana, 2024)
The objective of this article is to explain the determinants of access to credit in formal financial institutions for microenterprises by non-traditional factors, namely the possession of a mobile account without having an account in traditional financial institutions, the fact of being a member of a tontine or a mutual aid association. The methodology used is based on the estimation of the logit model with data from the Integrated Household Living Conditions Survey for 2019-2020 (EICVMB, 2019-2020) of the National Institute of Statistics of Burundi (INSBU). All other things being equal, the main results show that i) having a mobile banking account has a positive effect on access to credit (0.02751%), ii) even if the microentrepreneur does not have a traditional account (0.0322%), iii) and that being a member of a tontine or mutual aid association has a negative effect on access to credit (-0.02723%). For tontine groups to be a genuine source of finance for micro-businesses, especially those in rural areas, and thereby help to increase financial inclusion, these results call on the political authorities and financial service providers to work in synergy to develop the use of mobile banking in the provision of financial services, to develop appropriate support infrastructures, and to set up support modules for tontine groups, especially in rural areas. Keywords: Mobile Banking; Tontine or Mutual Aid Association; Financing; Microenterprise; Burundi